Experiences in the management of anastomotic leakages and analysis of the factors affecting leakage healing in patients with esophagogastric junction cancer - Ding, Ningning; Mao, Yousheng; He, Jie; Gao, Shugeng; Zhao, Yue; Yang, Ding; Sun, Kelin; Cheng, Guiyu; Mu, Juwei; Xue, Qi; Wang, Dali; Zhao, Jun; et al. (Journal of Thoracic Disease, 2017)
Background: It was reported in the literatures that the incidence of anastomotic leakage in patients with esophagogastric junction cancer decreased due to application of staplers and closure devices as well as gastric conduit technique in recent years, however, it increased slightly at our center since widely using the above devices and gastric conduit techniques from 2009. The objective of this study was to summarize our experiences in the management of anastomotic leakages and analyze the factors affecting leakage healing in the patients with esophagogastric junction cancer after surgical resection in recent 6 years. Methods: All patients who received surgical resections for esophagogastric junction cancer and diagnosed anastomotic leak at our center between January 2009 and December 2014 were retrospectively analyzed, we also enrolled the patients who had a longer hospital stay (>30 days) as they may develop anastomotic leak. The binary logistic regression in SPSS 16.0 was applied to analyze the factors that may affect leakage healing. Results: Of the 1,815 surgically treated esophagogastric junction cancer patients, 91 cases were diagnosed anastomotic leakage postoperatively. The patients were divided into two groups based on the median leakage healing time (40 days) in this series: fast healing group (37 cases) and slowly healing group (54 cases). All factors that may affect the leakage healing were put into analysis by using binary logistic regression. The results of the analysis showed that leakage size (OR =1.073, P=0.004), thoracic drainage (OR =12.937, P=0.037) and smoking index ≤400 (OR =1.001, P=0.04) significantly affected the healing time, while drinking history (P=0.177), duration of fever after anastomotic leak developed (P=0.084), and hypoproteinemia after leak (P=0.169) also apparently but not significantly affect the healing time. Conclusions: Though many factors may affect leakage healing in the esophagogastric junction carcinoma patients, leakage size, thoracic drainage and smoking index (≤400) are the most important factors affecting the leakage healing. Placement of a chest tube beside the anastomosis area during operation for early identification and control of an anastomotic leak to minimize contamination of the mediastinum is the most important way to promote leakage healing. A chest tube placing into the purulent cavities after the patients experienced leaks is also important for the cure of leakage. More attention should be paid perioperatively to the patients who had a smoking index (≥400) and the patients who suffered fever or hypoproteinemia.